Carl Schmitt's state and constitutional theory : a critical analysis - Schupmann, Benjamin A. (Oxford : Oxford University Press, 2018)
Schupmann appraises Schmitt's constitutional theory and examines how it was conceived in response to the Weimar Germany's legitimation crisis. Schmitt's normative theory of 'constrained' democracy offers a novel way to understand the legitimacy of liberal democracy and the limits of constitutional change, and is today more relevant than ever.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 7, 2017).
Keywords: Schmitt, Carl, -- 1888-1985.; State, The; Political science -- Philosophy; Germany -- History -- 1918-1933.; Politics and Government; Politics & government